(untitled) (E Conference Zone, 2022)
The water supplied through the pressure ducts always contains a certain amount of undissolved gases, a mixture of which is conventionally called the general term “air". This air enters the ducts through leaks in the pipe connections in the suction line to the pumps or in separate siphon sections operating under vacuum. Air is also sucked through the pump seals on the suction side, remains in the pipes when they are initially filled with water or when filling the pipes after repairs. A lot of air enters the water ducts together with water through water intakes, especially on rough mountain rivers. In addition, it is known that a large amount of gases contains groundwater..